The inorganic nutrient cost of building soil carbon. Issue 3 (4th May 2014) - Richardson, Alan E; Kirkby, Clive A; Banerjee, Samiran; Kirkegaard, John A
Abstract : " Inorganic nutrients are a hidden cost for sequestering carbon in soil organic matter."